HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN PJK DI POLI JANTUNG RSUD dr. SAIFUL ANWAR MALANG : Family Support Relationship with Compliance Drinking Medicine in CHD Patients in Cardiology Outpatient Department RSUD dr. Saiful Anwar Malang - Galih Aditya Putranto; Sih Ageng Lumadi; Rahmawati Maulida (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2022)
Coronary heart disease has an impact on patient medication adherence. Family support is one of the secondary prevention programs that is integrated with comprehensive care. It has been proven to be useful and effective in patients with CHD. The purpose of this study was to determine the relationship between family support and medication adherence in CHD patients at the heart polyclinic of RSUD Dr. Saiful Anwar Malang. The design of this research is correlational with a cross sectional study approach. The research population was 45 people, the sample was taken using purposive sampling with a sample of 41 respondents. Data collection techniques using a questionnaire. The data analysis method used is the Spearman Rank test using SPSS. This study proves high family support as many as 35 respondents (85.4) and has a high level of compliance as many as 36 people mostly (74.1%). Spearman rank test results obtained p value = (0.02) < (0.05). It was concluded that there was a relationship between family support and medication adherence in CHD patients at the heart polyclinic of RSUD Dr. Saiful Anwar Malang. Based on the results of the study to improve medication adherence, it is necessary to increase family support